Revealed comparative advantages and regional specialization: Evidence from Colombia in the Pacific Alliance - Rémi Stellian; Jenny Paola Danna-Buitrago (Journal of Applied Economics, 2019)
This paper is a methodological contribution to the calculation and use of Revealed Comparative Advantage (RCA) indexes. We first explain why the RCA index of Contribution to the Trade Balance (CTB) is theoretically relevant. However, as other RCA indexes might also be reliable measures of comparative advantages, we present standardized tools to compare RCA indexes computed for a given set of countries, products and periods. We illustrate with Colombia in the Pacific Alliance. In that case, the CTB index should be preferred to eight other representative RCA indexes. Therefore, the CTB index might be useful for empirical analysis, besides its theoretical relevance. Last, we suggest highlighting products that constitute strengths (weaknesses) for a country in international trade according to its ability to maintain through time the highest (lowest) CTB index compared with other countries. Again, we illustrate with Colombia in the Pacific Alliance and discuss implications for Colombian economic policy.
Keywords: 330; Colombia; Pacific Alliance; regional specialization; Revealed comparative advantage